Environmental analysis of the conservation status of the lower Pacoti River, Ceará State - Fiuza, Ana Beatriz Jucá de Queiroz; LeHugeur, Loreci Gislaine de Oliveira; Queiroz, Bruno Jucá (Arquivos de Ciências do Mar, 2010)
One of the main environmental problems of Ceara’s State is the coastal ecosystems’ degradation. The industrial and real estate activities have been causing damages to the environmental quality of rivers, mainly to the urban ones. The pollution and/or contamination provoked by non-treated sewage discharges are the most harmful environmental impact suffered by urban rivers. The non-treated sewage degrades the River Pacoti’s water quality and also harms the local communities. The Pacoti River runs across nine counties before its final draining at Aquiraz coasts, being the largest water stream that crosses Metropolitan Fortaleza. The percentage of basic sanitation among those counties is particularly low. The general objective of this research was to analyze the state of conservation of River Pacoti’s final section, accomplished through the execution of the following specific objectives: evaluate the water quality; characterize the use and occupation of the space; and identify the main environmental impacts caused by the effluents discharge. For that, a qualitative and descriptive research was conducted involving bibliographical, experimental and field surveys. Through the research it was concluded that the sewage released from industrial and real estate activities installed within Aquiraz County may cause water quality degradation impacting over the wild life, the vegetation and the life quality of the traditional populations that depend on the river’s resources to survive.